ANALISIS PENGARUH LONG-TERM RELATIONSHIP, INFORMATION SHARING, TRUST, DAN COOPERATION TERHADAP KINERJA SUPPLY CHAIN MANAGEMENT (Studi Pada Industri Bakpia di Provinsi D.I.Yogyakarta) - Rajasa Putra, Wahyu; Dwiyanto, Bambang Munas (Faculty of Economics and Business Diponegoro University, 2018)
The development of Indonesia's economy can not be separated from the existing industries in the areas scattered throughout Indonesia. Yogyakarta as one of districts has a potential and growing industrial sectors supported by the tourism sector located in the area. One of them is the bakpia industry in Ngampilan. Like other industries, the exhaust industry in Purbalingga also has problems such as capital difficulties, difficulties in product distribution, supply of raw materials for production and competition of similar products. These problems include into supply chain management. The purpose of this research is to examine the influence of long-term relationship, information sharing, trust, and cooperation on supply chain management performance.The population of this study is the company in the bakpiaÂ industry in Yogyakarta which amounted to 165. This research will use a sample of 100 respondents through questionnaires, where the data obtained will be analyzed include validity test, reliability test, classical assumption test, t test, and coefficient of determination testThe test results show that the indicators in this study are valid and reliable. The most influential variables are trust, then cooperation, then information sharing, and long-term relationship. These results show that all independent variables have a positive and significant influence on the dependent variable supply chain management performance.